Temporal disaggregation of the gross domestic product (GDP) for an island-region economy : the case of - Perry, Desmond R. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Seeks to develop consistent annual estimates of GDP for Trinidad and Tobago using data from the Value Added Tax (VAT) information system, sample surveys and other secondary sources for the period 1997 to 2004.